Preparation method of regenerated polyester fiber

By mixing recycled polyester fibers, modified wear-resistant agents, and composite modified carbon nanotubes, recycled polyester fibers with flame retardant, antibacterial and wear-resistant properties are prepared, which solves the problem of flammability of existing recycled polyester fibers, and realizes the efficient preparation of multifunctional fibers, meeting the interior textile needs of high-speed rail, aviation, automobile and other industries.

CN119824568AActive Publication Date: 2025-04-15JIANG SU KA LE FANG XIN CAI LIAO YOU XIAN GONG SI

Patent Information

Application Number
CN202411768374.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-15
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing recycled polyester fiber has a low limit oxygen index (LOI) and is a flammable fiber, which is difficult to meet the multifunctional needs such as flame retardant, antibacterial, and wear resistance. It is especially deficient in the application of interior textiles in the high-speed rail, aviation, automobile and other industries.

Method used

By mixing the recycled polyester fibers, modified wear-resistant agents, and composite modified carbon nanotubes, recycled polyester fibers with flame retardant, antibacterial and wear-resistant properties are prepared. The modified wear-resistant agent achieves antibacterial and flame retardant effects through the combination of Schiff alkali structure and phosphorus elements; the modifier improves the mechanical properties and wear resistance of the fiber through the cross-linking network structure; the hydroxylated carbon nanotubes enhance the wear resistance of the fiber by attracting the modifier in situ polymerization.

Benefits of technology

It realizes the wear resistance, antibacterial and flame retardant effects of recycled polyester fibers, significantly improves the mechanical and safety performance of the fibers, and can meet the multifunctional needs of interior textiles in high-speed rail, aviation, automobiles and other industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169585090000081
    Figure BDA0005169585090000081
Patent Text Reader

Abstract

The invention discloses a preparation method of regenerated polyester fibers, and relates to the technical field of polyester fibers. According to the invention, (4-formylphenyl) phosphonic acid and 2-(3-nitroaniline) acethydrazide are combined to form a Schiff base structure, so that an antibacterial effect is realized, and meanwhile, phosphorus is introduced, so that flame-retardant and anti-wear effects are realized; then, a modified wear-resistant agent with a cross-linked network structure is formed with butanediol, so that the wear-resistant effect of the fiber is remarkably enhanced; then 1, 7-octadiene-3-alcohol and octylene trichlorosilane are copolymerized to prepare a modifier, a cross-linked network structure is formed, the wear-resistant effect is enhanced, meanwhile, flame combustion can be inhibited, and the flame-retardant effect is achieved; then, the hydroxylated carbon nanotubes attract a modifier to be subjected to in-situ polymerization on the surfaces of the hydroxylated carbon nanotubes to prepare modified carbon nanotubes, so that the dispersity of the carbon nanotubes is improved, fiber falling is prevented, and the wear resistance of the material is improved; finally, the regenerated polyester fibers, the modified wear-resistant agent and the composite modified carbon nanotubes are mixed, melted and spun, so that the wear-resistant, antibacterial and flame-retardant effects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyester fibers, in particular to a method for preparing regenerated polyester fibers. Background Art

[0002] As society pays more and more attention to renewable energy, recycled polyethylene terephthalate (RPET) fibers have gradually been widely used. The application market of recycled polyester fiber products covers non-woven fabrics, home textiles, automobiles and other fields, with a wide range of products. However, due to the lack of attention to product development, the profit margin brought by the production of recycled polyester has been continuously compressed. Therefore, the development of fiber products with multiple functions and the increase of the added value of recycled polyester (RPET) fibers have gradually received attention from enterprises.

[0003] In recent years, there is a huge market demand for fiber products with flame retardant function. Multifunctional fibers that integrate flame retardant function and other functions have greatly increased the added value of fiber products, which can take the initiative in the increasingly fierce market competition. With the rapid development of the high-speed rail industry, aviation industry, and automobile industry, the requirements for interior textiles in high-speed rail, aircraft, and automobiles are getting higher and higher. The requirements for textiles in these fields are not only flame retardant properties, but more multifunctional products that integrate flame retardant function with health care function, such as flame retardant and antibacterial products, flame retardant wear-resistant products, flame retardant anion products, etc. However, the limiting oxygen index (LOI) of waste polyester materials is only 20% to 22%, which is a flammable fiber. Therefore, it is of great significance to recycle waste polyester and modify polyester materials for flame retardancy, antibacterial and wear resistance. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing regenerated polyester fiber to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing regenerated polyester fiber, comprising the following preparation steps:

[0006] (1) 10 to 20 parts of (4-formylphenyl)phosphonic acid, 8 to 16 parts of 2-(3-nitroaniline)acetylhydrazine, and 96 to 192 parts of anhydrous ethanol are mixed uniformly, heated to 74 to 80° C., and reacted for 5 to 7 hours under stirring at 100 rpm to obtain a crude product, which is purified to obtain a composite agent;

[0007] (2) 3 to 9 parts of the composite agent, 7 to 21 parts of butanediol, and 80 to 240 parts of toluene are mixed uniformly, heated to 100 to 110° C., stirred at 90 rpm for 6 to 8 hours, cooled to 25° C., and concentrated at a vacuum degree of -0.1 MPa and 40° C. for 4 to 6 hours to obtain a modified wear-resistant agent;

[0008] (3) Under a nitrogen atmosphere, 3 to 7 parts of 1,7-octadiene-3-ol, 8 to 12 parts of octene trichlorosilane, and 85 to 145 parts of toluene are mixed uniformly, the temperature is raised to 50 to 60° C., 5 to 9 parts of methylaluminoxane toluene solution are added dropwise at a rate of 1 drop / s, and the mixture is stirred at 80 rpm for 4 to 8 hours to obtain a reaction solution, which is crystallized to obtain a modifier;

[0009] (4) placing 14 to 22 parts of carbon nanotubes in a container, adding 32 to 50 parts of 15 wt% sulfuric acid and 28 to 46 parts of 15 wt% nitric acid, ultrasonicating at 20 to 30° C. for 1.5 to 2.5 hours, heating to 80 to 100° C. for reaction for 1 to 3 hours, filtering out the solid, washing it with deionized water for 3 times, and drying it in an oven at 45 to 55° C. for 6 to 10 hours to obtain hydroxylated carbon nanotubes;

[0010] (5) 12 to 36 parts of hydroxylated carbon nanotubes and 48 to 112 parts of tetrahydrofuran are mixed uniformly, and 6 to 14 parts of a modifier are added at 50 to 60° C. under nitrogen protection. After reacting for 12 to 30 hours, a solid product is collected, washed with tetrahydrofuran three times, and dried in an oven at 30 to 40° C. for 10 to 16 hours to obtain a composite modified carbon nanotube;

[0011] (6) adding 68 to 92 parts of waste polyester bottle chips, 10 to 14 parts of modified anti-wear agent, and 3 to 5 parts of composite modified carbon nanotubes into a mixer and mixing for 20 to 30 minutes, extruding through a mixing extruder, and slicing to obtain recycled polyester chips;

[0012] (7) The regenerated polyester chips are pre-crystallized and dried at 90-100° C., melted and ejected at 275-295° C. in a spinning machine, cooled, and stretched in a stretching machine to 2.0-2.4 times, then curled at 150-170° C., relaxed and heat-set at 200-220° C., and cut to obtain regenerated polyester fibers.

[0013] Furthermore, the purification step of step (1) is as follows: add 1 part of the crude product to 6 parts of ethanol, stir at 100 rpm for 10 to 30 minutes, filter out the solid, repeat twice, add 10 parts of deionized water, stir at 90 rpm for 20 to 40 minutes, filter out the solid, wash it 3 times with deionized water, and dry it in an oven at 45 to 55°C for 10 to 16 hours.

[0014] Furthermore, the content of methylaluminoxane in the methylaluminoxane toluene solution in step (3) is 5 wt%.

[0015] Furthermore, the crystallization step in step (3) is as follows: adding 1 part of the reaction solution to 4 parts of hydrochloric acid ethanol solution, stirring at 120 rpm for 20 to 40 minutes, filtering out the solid, washing it alternately with anhydrous ethanol and deionized water for 3 times, and drying it in an oven at 45 to 55°C for 8 to 12 hours.

[0016] Furthermore, the content of hydrochloric acid in the hydrochloric acid ethanol solution is 20wt%.

[0017] Furthermore, in step (6), the temperature of the mixer is 230-240°C.

[0018] Furthermore, the parameters of the mixing extruder in step (6) are: head temperature 280-290° C., screw speed 160-220 r / min, and extrusion pressure 6-10 MPa.

[0019] Furthermore, the cooling in step (7) is performed at a cooling air temperature of 15 to 19° C., a wind speed of 0.8 to 1.6 m / s, a wind pressure of 500 to 700 Pa, and a cooling time of 10 to 20 min.

[0020] Furthermore, the nozzle pressure of the spraying in step (7) is 0.3-0.5 MPa.

[0021] Furthermore, in step (7), the temperature of the drawing machine is 200-230° C. and the winding speed is 1300-1500 m / min.

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0023] The invention achieves the effects of wear resistance, antibacterial and flame retardancy by mixing recycled polyester fiber, modified wear-resistant agent and composite modified carbon nanotubes for melt spinning.

[0024] First, the modified wear-resistant agent combines the aldehyde group of (4-formylphenyl)phosphonic acid with the amino group of 2-(3-nitroaniline)acetylhydrazine to form a Schiff base structure, which can combine with the ribosome of bacteria to prevent the bacteria from synthesizing proteins and achieve an antibacterial effect. At the same time, the phosphorus element is introduced to decompose during combustion to generate non-combustible products such as phosphates and phosphate esters, thereby achieving a flame retardant effect. The hydrazide structure is assisted to generate a tribochemical reaction during metal friction to generate nitrogen-containing compounds with low shear strength, thereby improving the wear resistance of the fiber. On this basis, the presence of the benzene ring can significantly improve the thermal stability of the wear-resistant agent and indirectly improve the flame retardant effect of the fiber. Then, it is dehydrated and condensed with butanediol to form a cross-linked network structure, which significantly enhances the mechanical properties of the fiber, and can deform and bend under the action of external force, thereby achieving a wear-resistant effect.

[0025] Secondly, 1,7-octadien-3-ol and octene trichlorosilane are copolymerized to form a modifier to form a cross-linked network structure, improve the shear resistance, thereby increasing the stability of the connection and preliminarily improving the wear resistance of the fiber. The long-chain alkane molecules of octene trichlorosilane can enhance the adsorption stability of the molecules, thereby enhancing the wear resistance. At the same time, the presence of trichlorosilane makes the silicon element form a glass-like film covering the fiber surface when combustion occurs, isolating the heat and oxygen from entering, and cooperating with the chlorine element to decompose and produce gas to form a porous foam layer, thereby inhibiting the combustion of the flame and achieving a flame retardant effect; then, the hydroxylated carbon nanotubes are used to attract the modifier to polymerize in situ on its surface, improving the dispersion of the carbon nanotubes while promoting the formation of an intertwined structure between the carbon nanotubes and the fiber molecules, preventing the fiber from falling off on the friction surface, thereby improving the wear resistance of the material. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the regenerated polyester fibers prepared in the following examples.

[0028] Breaking strength: The same weight of the embodiment and the comparative example were tested according to GB / T 14337.

[0029] Wear amount: Take the same weight of the embodiment and the comparative example, test the wear resistance of the plastic with reference to GB / T 3960, and record the wear mass.

[0030] Antibacterial rate: Take the same weight of the embodiment and the comparative example, and make the composite fiber non-woven fabric of the same specification (weight 400g / m 2 ) fabrics, tested according to GB / T 20944.3.

[0031] Limiting oxygen index: Take the same weight of the embodiment and the comparative example, and make the composite fiber non-woven fabric of the same specification (weight 400g / m 2 ) fabrics, tested according to ISO4589-2.

[0032] Example 1: (1) 10 parts of (4-formylphenyl)phosphonic acid, 8 parts of 2-(3-nitroaniline)acetylhydrazine and 96 parts of anhydrous ethanol were mixed uniformly, heated to 74°C, and reacted at 100 rpm for 5 hours to obtain a crude product. 1 part of the crude product was added to 6 parts of ethanol, stirred at 100 rpm for 10 minutes, and the solid was filtered out. This was repeated twice. 10 parts of deionized water were added, stirred at 90 rpm for 20 minutes, and the solid was filtered out. The solid was washed three times with deionized water and dried in a 45°C oven for 10 hours to obtain a composite agent.

[0033] (2) 3 parts of the composite agent, 7 parts of butanediol and 80 parts of toluene were mixed evenly, heated to 100°C, reacted at 90 rpm for 6 hours, cooled to 25°C, and concentrated at -0.1 MPa and 40°C for 4 hours to obtain a modified wear-resistant agent;

[0034] (3) Under a nitrogen atmosphere, 3 parts of 1,7-octadien-3-ol, 8 parts of octene trichlorosilane, and 85 parts of toluene were mixed uniformly, the temperature was raised to 50° C., 5 parts of 5 wt% methylaluminoxane toluene solution were added dropwise at a rate of 1 drop / s, and the mixture was stirred at 80 rpm for 4 h to obtain a reaction solution, 1 part of the reaction solution was added to 4 parts of 20 wt% hydrochloric acid ethanol solution, and the mixture was stirred at 120 rpm for 20 min. The solid was filtered and washed three times with anhydrous ethanol and deionized water alternately, and dried in an oven at 45° C. for 8 h to obtain a modifier;

[0035] (4) placing 14 parts of carbon nanotubes in a container, adding 32 parts of 15 wt% sulfuric acid and 28 parts of 15 wt% nitric acid, ultrasonicating at 20°C for 1.5 hours, heating to 80°C for 1 hour, filtering out the solid, washing it with deionized water for 3 times, and drying it in an oven at 45°C for 6 hours to obtain hydroxylated carbon nanotubes;

[0036] (5) 12 parts of hydroxylated carbon nanotubes and 48 parts of tetrahydrofuran were mixed evenly, and 6 parts of modifier were added at 50° C. under nitrogen protection. After reacting for 12 hours, the solid product was collected, washed with tetrahydrofuran three times, and dried in an oven at 30° C. for 10 hours to obtain composite modified carbon nanotubes;

[0037] (6) adding 68 parts of waste polyester bottle chips, 10 parts of modified anti-wear agent, and 3 parts of composite modified carbon nanotubes into a mixer and mixing at 230° C. for 20 min, extruding through a mixing extruder with a head temperature of 280° C., a screw speed of 160 r / min, and an extrusion pressure of 6 MPa, and slicing to obtain recycled polyester chips;

[0038] (7) The regenerated polyester chips were pre-crystallized and dried at 90°C, melted at 275°C in a spinning machine, ejected at a pressure of 0.3 MPa, cooled for 10 min at a cooling air temperature of 15°C, a wind speed of 0.8 m / s, and a wind pressure of 500 Pa, and stretched in a stretching machine to 2.0 times, wherein the temperature of the stretching machine was 200°C and the winding speed was 1300 m / min, and then curled at 150°C, relaxed and heat-set at 200°C, and cut to obtain regenerated polyester fibers.

[0039] Example 2: (1) 15 parts of (4-formylphenyl)phosphonic acid, 12 parts of 2-(3-nitroaniline)acetylhydrazine and 144 parts of anhydrous ethanol were mixed uniformly, heated to 77°C, and reacted at 100 rpm for 6 hours to obtain a crude product. 1 part of the crude product was added to 6 parts of ethanol, stirred at 100 rpm for 20 minutes, and the solid was filtered out. This was repeated twice. 10 parts of deionized water were added, and the solid was stirred at 90 rpm for 30 minutes. The solid was filtered out, washed with deionized water 3 times, and dried in a 50°C oven for 13 hours to obtain a composite agent.

[0040] (2) 6 parts of the composite agent, 14 parts of butanediol and 160 parts of toluene were mixed evenly, heated to 105°C, reacted for 7 hours under stirring at 90 rpm, cooled to 25°C, and concentrated at a vacuum degree of -0.1 MPa and 40°C for 5 hours to obtain a modified wear-resistant agent;

[0041] (3) Under a nitrogen atmosphere, 5 parts of 1,7-octadien-3-ol, 10 parts of octene trichlorosilane, and 115 parts of toluene were mixed uniformly, the temperature was raised to 55° C., 7 parts of 5 wt% methylaluminoxane toluene solution were added dropwise at a rate of 1 drop / s, and the mixture was stirred at 80 rpm for 6 h to obtain a reaction solution, 1 part of the reaction solution was added to 4 parts of 20 wt% hydrochloric acid ethanol solution, and the mixture was stirred at 120 rpm for 30 min. The solid was filtered and washed three times with anhydrous ethanol and deionized water alternately, and dried in an oven at 50° C. for 10 h to obtain a modifier;

[0042] (4) placing 18 parts of carbon nanotubes in a container, adding 41 parts of 15 wt% sulfuric acid and 37 parts of 15 wt% nitric acid, ultrasonicating at 25°C for 2.0 h, heating to 90°C for reaction for 2 h, filtering out the solid, washing it with deionized water three times, and drying it in an oven at 50°C for 8 h to obtain hydroxylated carbon nanotubes;

[0043] (5) 24 parts of hydroxylated carbon nanotubes and 80 parts of tetrahydrofuran were mixed evenly, and 10 parts of a modifier were added at 55° C. under nitrogen protection. After reacting for 21 hours, the solid product was collected, washed with tetrahydrofuran three times, and dried in an oven at 35° C. for 13 hours to obtain a composite modified carbon nanotube;

[0044] (6) adding 80 parts of waste polyester bottle chips, 12 parts of modified anti-wear agent, and 4 parts of composite modified carbon nanotubes into a mixer and mixing at 235° C. for 25 min, extruding through a mixing extruder with a head temperature of 285° C., a screw speed of 190 r / min, and an extrusion pressure of 8 MPa, and slicing to obtain recycled polyester chips;

[0045] (7) The regenerated polyester chips were pre-crystallized and dried at 95°C, melted at 285°C in a spinning machine, ejected at a pressure of 0.4 MPa, cooled for 15 min at a cooling air temperature of 17°C, a wind speed of 1.2 m / s, and a wind pressure of 600 Pa, and stretched in a drawing machine to 2.2 times, wherein the temperature of the drawing machine was 215°C and the winding speed was 1400 m / min, and then curled at 160°C, relaxed and heat-set at 210°C, and cut to obtain regenerated polyester fibers.

[0046] Example 3: (1) 20 parts of (4-formylphenyl)phosphonic acid, 16 parts of 2-(3-nitroaniline)acetylhydrazine and 192 parts of anhydrous ethanol were mixed uniformly, heated to 80°C, and reacted at 100 rpm for 7 hours to obtain a crude product. One part of the crude product was added to 6 parts of ethanol, stirred at 100 rpm for 30 minutes, and the solid was filtered out. This was repeated twice. 10 parts of deionized water were added, and the solid was stirred at 90 rpm for 40 minutes. The solid was filtered out, washed with deionized water 3 times, and dried in a 55°C oven for 16 hours to obtain a composite agent.

[0047] (2) 9 parts of the composite agent, 21 parts of butanediol and 240 parts of toluene were mixed evenly, heated to 110° C., reacted at 90 rpm for 8 h, cooled to 25° C., and concentrated at -0.1 MPa and 40° C. for 6 h to obtain a modified anti-wear agent;

[0048] (3) Under a nitrogen atmosphere, 7 parts of 1,7-octadien-3-ol, 12 parts of octene trichlorosilane, and 145 parts of toluene were mixed uniformly, the temperature was raised to 60° C., 9 parts of 5 wt% methylaluminoxane toluene solution were added dropwise at a rate of 1 drop / s, and the mixture was stirred at 80 rpm for 8 h to obtain a reaction solution, 1 part of the reaction solution was added to 4 parts of 20 wt% hydrochloric acid ethanol solution, and the mixture was stirred at 120 rpm for 40 min. The solid was filtered and washed three times with anhydrous ethanol and deionized water alternately, and dried in an oven at 55° C. for 12 h to obtain a modifier;

[0049] (4) placing 22 parts of carbon nanotubes in a container, adding 50 parts of 15 wt% sulfuric acid and 46 parts of 15 wt% nitric acid, ultrasonicating at 30°C for 2.5 hours, heating to 100°C for reaction for 3 hours, filtering out the solid, washing it with deionized water for 3 times, and drying it in an oven at 55°C for 10 hours to obtain hydroxylated carbon nanotubes;

[0050] (5) 36 parts of hydroxylated carbon nanotubes and 112 parts of tetrahydrofuran were mixed evenly, and 14 parts of a modifier were added at 60° C. under nitrogen protection. After reacting for 30 hours, the solid product was collected, washed with tetrahydrofuran three times, and dried in an oven at 40° C. for 16 hours to obtain a composite modified carbon nanotube;

[0051] (6) adding 92 parts of waste polyester bottle flakes, 14 parts of modified anti-wear agent, and 5 parts of composite modified carbon nanotubes into a mixer and mixing at 240° C. for 30 min, extruding through a mixing extruder with a head temperature of 290° C., a screw speed of 220 r / min, and an extrusion pressure of 10 MPa, and slicing to obtain recycled polyester chips;

[0052] (7) The regenerated polyester chips were pre-crystallized and dried at 100°C, melted at 295°C in a spinning machine, ejected at a pressure of 0.5 MPa, cooled for 20 min at a cooling air temperature of 19°C, a wind speed of 1.6 m / s, and a wind pressure of 700 Pa, and stretched in a drawing machine to 2.4 times, wherein the temperature of the drawing machine was 230°C and the winding speed was 1500 m / min, and then curled at 170°C, relaxed and heat-set at 220°C, and cut to obtain regenerated polyester fibers.

[0053] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that there is no step (1), and step (2) is changed to: 6 parts of 2-(3-nitroaniline) acetic hydrazide, 14 parts of butanediol, and 160 parts of toluene are mixed uniformly, heated to 105° C., reacted at 90 rpm for 7 hours, cooled to 25° C., and concentrated at a vacuum degree of -0.1 MPa and 40° C. for 5 hours to obtain a modified anti-wear agent. The remaining steps are the same as in Example 2.

[0054] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that there is no step (1), and step (2) is changed to: 6 parts of (4-formylphenyl)phosphonic acid, 14 parts of butanediol, and 160 parts of toluene are mixed uniformly, heated to 105° C., reacted at 90 rpm for 7 hours, cooled to 25° C., and concentrated at a vacuum degree of -0.1 MPa and 40° C. for 5 hours to obtain a modified anti-wear agent. The remaining steps are the same as in Example 2.

[0055] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that there is no step (2), and step (6) is changed to: 80 parts of waste polyester bottle chips, 12 parts of compounding agent, and 4 parts of composite modified carbon nanotubes are added to a mixer and mixed at 235° C. for 25 minutes, and extruded through a mixing extruder with a head temperature of 285° C., a screw speed of 190 r / min, and an extrusion pressure of 8 MPa, and sliced ​​to obtain recycled polyester chips. The remaining steps are the same as in Example 2.

[0056] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that there are no steps (1) and (2), and step (6) is changed to: 80 parts of waste polyester bottle chips, 2 parts of (4-formylphenyl)phosphonic acid, 1 part of 2-(3-nitroaniline)acetylhydrazine, 7 parts of butanediol, and 4 parts of composite modified carbon nanotubes are added to a mixer and mixed at 235° C. for 25 minutes, and extruded through a mixing extruder with a head temperature of 285° C., a screw speed of 190 r / min, and an extrusion pressure of 8 MPa, and sliced ​​to obtain recycled polyester chips. The remaining steps are the same as in Example 2.

[0057] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that there is no step (3), and step (5) is changed to: 24 parts of hydroxylated carbon nanotubes and 80 parts of tetrahydrofuran are mixed evenly, 10 parts of octene trichlorosilane are added at 55° C. under nitrogen protection, and the solid product is collected after reacting for 21 hours, washed with tetrahydrofuran three times, and dried in an oven at 35° C. for 13 hours to obtain composite modified carbon nanotubes. The remaining steps are the same as in Example 2.

[0058] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that there is no step (3), and step (5) is changed to: 24 parts of hydroxylated carbon nanotubes and 80 parts of tetrahydrofuran are mixed evenly, 10 parts of 1,7-octadiene-3-ol are added at 55° C. under nitrogen protection, and the solid product is collected after reacting for 21 hours, washed with tetrahydrofuran three times, and dried in an oven at 35° C. for 13 hours to obtain a composite modified carbon nanotube. The remaining steps are the same as in Example 2.

[0059] Effect example

[0060] The following Table 1 shows the performance analysis results of the regenerated polyester fibers of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.

[0061] Table 1

[0062]

[0063] From the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 1, it can be found that by using (4-formylphenyl)phosphonic acid to introduce phosphorus element, the decomposition reaction during combustion generates non-combustible products such as phosphates and phosphate ester salts, thereby achieving a flame retardant effect; from the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 2, it can be found that through the hydrazide structure in 2-(3-nitroaniline)acetohydrazide, a tribochemical reaction occurs during metal friction to generate nitrogen-containing compounds with low shear strength, thereby improving the wear resistance of the fiber. At the same time, the presence of the benzene ring can significantly improve the thermal stability of the wear-resistant agent and improve the flame retardant effect of the fiber; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 3, it can be found that by dehydration condensation with butanediol, a cross-linked network structure is formed, which significantly enhances the mechanical properties of the fiber, and can be deformed and bent under the action of external force, thereby achieving a wear-resistant effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 4, it can be found that Now, the aldehyde group of (4-formylphenyl)phosphonic acid is combined with the amino group of 2-(3-nitroaniline)acetohydrazide to form a Schiff base structure, which can bind to the ribosome of bacteria, prevent the process of bacterial protein synthesis, and play an antibacterial effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 5, it can be found that the use of 1,7-octadiene-3-ol to participate in the polymerization reaction can form a cross-linked network structure, improve shear resistance, increase connection stability, and improve fiber wear resistance; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 6, it can be found that the long-chain alkane molecules of octene trichlorosilane can enhance the adsorption stability of the molecule and enhance the wear resistance. At the same time, the presence of trichlorosilane makes it possible that when combustion occurs, the silicon element is heated to form a glass-like film covering the fiber surface, isolating heat and oxygen from entering, and cooperates with the chlorine element to decompose and produce gas to form a porous foam layer, which can inhibit the combustion of the flame and achieve a flame retardant effect.

[0064] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing regenerated polyester fiber, characterized in that: The method comprises the following preparation steps: (1) 10 to 20 parts of (4-formylphenyl)phosphonic acid, 8 to 16 parts of 2-(3-nitroaniline)acetylhydrazine, and 96 to 192 parts of anhydrous ethanol are mixed uniformly, heated to 74 to 80° C., and reacted for 5 to 7 hours under stirring at 100 rpm to obtain a crude product, which is purified to obtain a composite agent; (2) 3 to 9 parts of the composite agent, 7 to 21 parts of butanediol, and 80 to 240 parts of toluene are mixed uniformly, heated to 100 to 110° C., stirred at 90 rpm for 6 to 8 hours, cooled to 25° C., and concentrated at a vacuum degree of -0.1 MPa and 40° C. for 4 to 6 hours to obtain a modified wear-resistant agent; (3) Under a nitrogen atmosphere, 3 to 7 parts of 1,7-octadiene-3-ol, 8 to 12 parts of octene trichlorosilane, and 85 to 145 parts of toluene are mixed uniformly, the temperature is raised to 50 to 60° C., 5 to 9 parts of methylaluminoxane toluene solution are added dropwise at a rate of 1 drop / s, and the mixture is stirred at 80 rpm for 4 to 8 hours to obtain a reaction solution, which is crystallized to obtain a modifier; (4) placing 14 to 22 parts of carbon nanotubes in a container, adding 32 to 50 parts of 15 wt% sulfuric acid and 28 to 46 parts of 15 wt% nitric acid, ultrasonicating at 20 to 30° C. for 1.5 to 2.5 hours, heating to 80 to 100° C. for reaction for 1 to 3 hours, filtering out the solid, washing it with deionized water for 3 times, and drying it in an oven at 45 to 55° C. for 6 to 10 hours to obtain hydroxylated carbon nanotubes; (5) 12 to 36 parts of hydroxylated carbon nanotubes and 48 to 112 parts of tetrahydrofuran are mixed uniformly, and 6 to 14 parts of a modifier are added at 50 to 60° C. under nitrogen protection. After reacting for 12 to 30 hours, a solid product is collected, washed with tetrahydrofuran three times, and dried in an oven at 30 to 40° C. for 10 to 16 hours to obtain a composite modified carbon nanotube; (6) adding 68 to 92 parts of waste polyester bottle chips, 10 to 14 parts of modified anti-wear agent, and 3 to 5 parts of composite modified carbon nanotubes into a mixer and mixing for 20 to 30 minutes, extruding through a mixing extruder, and slicing to obtain recycled polyester chips; (7) The regenerated polyester chips are pre-crystallized and dried at 90-100° C., melted and ejected at 275-295° C. in a spinning machine, cooled, and stretched in a stretching machine to 2.0-2.4 times, then curled at 150-170° C., relaxed and heat-set at 200-220° C., and cut to obtain regenerated polyester fibers.

2. The method for preparing a regenerated polyester fiber according to claim 1, characterized in that: The purification step in step (1) is as follows: add 1 part of the crude product to 6 parts of ethanol, stir at 100 rpm for 10 to 30 minutes, filter out the solid, repeat twice, add 10 parts of deionized water, stir at 90 rpm for 20 to 40 minutes, filter out the solid, wash it 3 times with deionized water, and dry it in an oven at 45 to 55°C for 10 to 16 hours.

3. The method for preparing a regenerated polyester fiber according to claim 1, characterized in that: The content of methylaluminoxane in the methylaluminoxane toluene solution in step (3) is 5wt%.

4. The method for preparing a regenerated polyester fiber according to claim 1, characterized in that: The crystallization step in step (3) is as follows: add 1 part of the reaction solution to 4 parts of hydrochloric acid ethanol solution, stir at 120 rpm for 20 to 40 minutes, filter out the solid, wash it alternately with anhydrous ethanol and deionized water for 3 times, and dry it in an oven at 45 to 55°C for 8 to 12 hours.

5. The method for preparing a regenerated polyester fiber according to claim 4, characterized in that: The content of hydrochloric acid in the hydrochloric acid ethanol solution is 20wt%.

6. The method for preparing a regenerated polyester fiber according to claim 1, characterized in that: The mixer temperature in step (6) is 230-240°C.

7. The method for preparing a regenerated polyester fiber according to claim 1, characterized in that: The parameters of the mixing extruder in step (6) are: head temperature 280-290° C., screw speed 160-220 r / min, and extrusion pressure 6-10 MPa.

8. The method for preparing a regenerated polyester fiber according to claim 1, characterized in that: The cooling in step (7) is performed at a cooling air temperature of 15 to 19° C., a wind speed of 0.8 to 1.6 m / s, a wind pressure of 500 to 700 Pa, and a cooling time of 10 to 20 min.

9. The method for preparing a regenerated polyester fiber according to claim 1, characterized in that: The nozzle pressure of the spraying in step (7) is 0.3-0.5 MPa.

10. The method for preparing regenerated polyester fiber according to claim 1, characterized in that: In step (7), the temperature of the drawing machine is 200-230° C. and the winding speed is 1300-1500 m / min.

Citation Information

Patent Citations

  • Preparation method of easy-to-dye polyester fibers

    CN108517579A

  • Thermosetting polyester, preparation method and application

    CN115651192A

  • Antibacterial flame-retardant polyamide fiber material and preparation method thereof

    CN117107388A

  • Flame-retardant antistatic composite modified polyester fiber and preparation method thereof

    CN118745608A

  • Conductive polyester composition

    US20230088098A1

Cited By

  • Toughened wear-resistant polyester fiber and application thereof

    CN121653873A

  • A toughened and abrasion-resistant polyester fiber and its application

    CN121653873B